Promoting Origination of Dynamicity of Non-Cellular Cognizers - Pogossian, Edward M. (Mathematical Problems of Computer Science, 2023)
Dynamic realities exist at the most basic level of elementary particles, which, according to quantum field theory emerge as excitations of fundamental quantum fields. At the same time, the nuclei of cognizers – doers, and their modes -1/2place classifiers and energizers, are also types of dynamic realities. Trying to trace the origin of the dynamicity of doers to the dynamics of particles and fields would help enlighten the origination of classifiers in nature. As a footstep to a positive answer to this question, we provide cases of such interpretation of dynamicity concluding by some hints to generalize the cases.